Time course of 23Na signal intensity after myocardial infarction in humans. - Sandstede, J; Hillenbrand, H; Beer, M; Pabst, T; Butter, F; Machann, W; Bauer, W; Hahn, D; Neubauer, S (2004)
Experimental studies demonstrated persistently increased 23Na content in nonviable myocardium post-myocardial infarction (MI). We hypothesized that nonviable myocardium in humans would show elevated 23Na content at all stages of infarct development, and therefore could be imaged with 23Na MRI. Ten patients were examined on days 4, 14, and 90 after infarction, and five of these patients participated in a 12-month follow-up. Double angulated short-axis cardiac 23Na images were obtained with the use of a 23Na surface coil and an ECG-triggered, 3D gradient-echo sequence. 1H T2-weighted imaging (N = 9) was performed on days 4, 14, and 90. Wall motion was assessed by cine MRI, and the infarct size was determined by late enhancement on day 90. The 23Na signal intensity (SI) of infarcted myocardium was expressed as the percentage increase over 23Na SI of noninfarcted myocardium. All of the patients showed an area of elevated SI on 23Na and 1H T2-weighted images that correlated with wall motion abnormalities and late enhancement. 23Na SI was highest on day 4. It then decreased until day 90, but remained elevated (39% +/- 18%, 31% +/- 17%, 28% +/- 13% on days 4, 14, and 90, respectively, P = 0.001). No further decrease was found 1 year after infarction (25% +/- 7%, P = 0.89 vs. day 90). 1H T2-weighted SI decreased between days 4 and 14, but on day 90 only six of nine patients had a residual elevated SI. Thus, 23Na SI is elevated in nonviable infarction at all time points following MI, and 23Na MRI may become a suitable technique for imaging nonviable myocardium in humans.